2021
DOI: 10.3389/fphar.2020.620906
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic and Bleeding Events of Ticagrelor Monotherapy in Korean Patients With and Without Diabetes Mellitus: Insights From the TICO Trial

Abstract: Background: Ticagrelor monotherapy after 3 months dual antiplatelet therapy (DAPT) with aspirin and ticagrelor can reduce bleeding without increasing ischemic events after percutaneous coronary intervention (PCI). However, the impact of this approach among the patient with diabetes remains unknown.Methods: This was a sub-analysis of the Ticagrelor Monotherapy after 3 months in the Patients Treated with New Generation Sirolimus Eluting Stent for Acute Coronary Syndrome (TICO) trial. After successful PCI, the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Through consideration of the reference lists of these studies, a total of 9 reports for 8 trials were ultimately deemed eligible for inclusion in our systematic review and meta-analysis. [11][12][13][14][15][16][17][18][19] Our systematic search of literature is depicted in Preferred Reporting Items for Systematic Reviews and Meta-Analyses flowchart (see Figure, Supplemental Digital Content 1, http://links.lww.com/JCVP/B8).…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through consideration of the reference lists of these studies, a total of 9 reports for 8 trials were ultimately deemed eligible for inclusion in our systematic review and meta-analysis. [11][12][13][14][15][16][17][18][19] Our systematic search of literature is depicted in Preferred Reporting Items for Systematic Reviews and Meta-Analyses flowchart (see Figure, Supplemental Digital Content 1, http://links.lww.com/JCVP/B8).…”
Section: Search Resultsmentioning
confidence: 99%
“…The TICO substudy did not provide data on the primary end point, and thus, it was necessary to obtain this information from the main trial report. 16 We extracted data on the primary end point by analyzing the entire population of diabetic patients enrolled in the RESET trial. 11 However, because of limited availability, data on other outcomes were only accessible from the diabetic subset of the study.…”
Section: Studies and Patients' Characteristicsmentioning
confidence: 99%
“…Thereafter, only 112 full-text articles were assessed for eligibility. On the basis of the inclusion and exclusion criteria, further studies were eliminated due to the following reasons: Finally, only five studies [13][14][15][16][17] based on randomized trials were selected for this analysis.…”
Section: Search Resultsmentioning
confidence: 99%
“…The results demonstrated that ticagrelor monotherapy administered after 3-month of DAPT was significantly associated with a reduced risk of major bleeding without increasing the risk of major adverse cardio-cerebrovascular events compared to ticagrelor-based 12-month DAPT. This benefit was particularly observed in specific high-risk patient groups, such as those with ST-segment elevation myocardial infarction, diabetes, elderly patients, and obesity (19)(20)(21)(22). Our study also demonstrated that ticagrelor monotherapy was not significantly associated with an increased incidence of ischemic events, including TLF and stent thrombosis, and it was not associated with and elevated bleeding risk in patients with small vessel disease.…”
Section: Discussionmentioning
confidence: 99%